2002
DOI: 10.1159/000063573
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Enzyme Activities and Malondialdehyde Levels in Patients with Obsessive-Compulsive Disorder

Abstract: To examine the importance of free radicals in the pathogenesis of obsessive-compulsive disorder (OCD), we aimed to evaluate whether malondialdehyde (MDA), a product of lipid peroxidation, and antioxidant enzyme [superoxide dismutase (SOD), glutathione peroxidase (GSH-Px) and catalase (CAT)] activity levels were associated with OCD. The patients were divided into two subgroups according to whether DSM-IV major depressive disorder (MDD) was accompanied (OCD + MDD) or not (OCD – MDD). The MDA and antioxidant enzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
94
1
5

Year Published

2005
2005
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(104 citation statements)
references
References 31 publications
4
94
1
5
Order By: Relevance
“…Similarly, a significant decrease in plasma ascorbate in the pretreatment group signified a compromised ascorbate in the brain tissues. Ascorbate has been found to play the role of chief antioxidant in the brain in several earlier studies (11) and its compromised level has been found to be associated with several neurological and psychiatric diseases (17,18,19). In our present study the reduced plasma ascorbate in the pretreatment group, thus, could be suggested due to an increased lipid peroxidation in brain tissues of OCD patients.…”
Section: Discussionsupporting
confidence: 59%
“…Similarly, a significant decrease in plasma ascorbate in the pretreatment group signified a compromised ascorbate in the brain tissues. Ascorbate has been found to play the role of chief antioxidant in the brain in several earlier studies (11) and its compromised level has been found to be associated with several neurological and psychiatric diseases (17,18,19). In our present study the reduced plasma ascorbate in the pretreatment group, thus, could be suggested due to an increased lipid peroxidation in brain tissues of OCD patients.…”
Section: Discussionsupporting
confidence: 59%
“…The serum concentration of MDA was significantly higher and that of vitamin C was significantly lower in Schizophrenic patients. 26 Similar findings were also found in obsessive-compulsive disorder 14,27,28 and in panic disorder. 29 …”
Section: Parameterssupporting
confidence: 76%
“…34 Cholesterol deficiency in neuronal membranes may also have a direct negative impact on synapse formation, dendritic outgrowth, and neuronal survival. 35 Moreover, as several studies have 36,37 shown that OCD patients may have increased oxidative stress and that this correlates with disease severity, we may speculate that lipid peroxidation might be one of the causes of reduced serum HDL-C and altered lipid profile in these patients. Alexithymia probably results from an inhibitory mechanism that could contribute to a suppression of emotional processing within the right hemisphere and to poorer verbalization of emotional contents (within the left hemisphere).…”
Section: Discussionmentioning
confidence: 92%